QUIC-fire: A fast-running simulation tool for prescribed fire planning. (March 2020) - Linn, R.R.; Goodrick, S.L.; Brambilla, S.; Brown, M.J.; Middleton, R.S.; O'Brien, J.J.; Hiers, J.K.
Abstract: Coupled fire-atmospheric modeling tools are increasingly used to understand the complex and dynamic behavior of wildland fires. Multiple research tools linking combustion to fluid flow use Navier-Stokes numerical solutions coupled to a thermodynamic model to understand fire-atmospheric feedbacks, but these computational fluid dynamics approaches require high-performance computing resources. We present a new simulation tool called QUIC-Fire to rapidly solve these feedbacks by coupling the mature 3-D rapid wind solver QUIC-URB to a physics-based cellular automata fire spread model Fire-CA. QUIC-Fire uses 3-D fuels inputs similar to the CFD model FIRETEC, allowing this tool to simulate effects of fuel structure on local winds and fire behavior. Results comparing fire behavior metrics to the computational fluid dynamic model FIRETEC show strong agreement. QUIC-Fire is the first tool intended to provide an opportunity for prescribed fire planners to compare, evaluate, and design burn plans, including complex ignition patterns and coupled fire-atmospheric feedbacks. Highlights: New coupled fire/atmosphere modeling tool that is applicable to prescribed fire called QUIC-Fire. Two way fire/atmosphere feedback achieved by coupling QUIC-URB wind solver with a cellular automata fire behavior model. Much faster and computationally less expensive than CFD-based models. Preliminary results comparing QUIC-Fire and FIRETEC (CFD-based fire/atmosphere model) are encouraging.